Three Faces of the PKS Political Party in the Formulation of the New Energy and Renewable Energy Bill - Wiguna, Bangkit Adhi; Lay, Dhivana Anarchia Ria; Mayasari, Diana; Leonard, Edo Christian (PCD Journal, 2023)
Political parties play an important role in aggregating people's interests, including in the formulation of the New Energy and Renewable Energy Bill (RUU EBET) or the EBET Bill, both at the central and regional levels. This study aims to look at the dynamics between the three faces of a political party, namely the party in the public office, central office, and at the grassroots level (Katz & Mair 1993), during the formulation of RUU EBET or the EBET Bill. Using the Prosperous Justice Party (PKS) as a case study, this research finds that parties in the public and central office actually depoliticize the roles of parties at the grassroots level. This depoliticization manifests itself in three ways: (1) assumptions about the inability of party structures at the regional level to discuss the EBET issues, (2) not including the interests of developing EBET at the regional level as part of the EBET Bill, and (3) narrow definitions and restrictions of the EBET Bill as a central and elite issue.